Perancangan Mesin Grinder-Rollpress Untuk Pengolahan Pasta Ubi Kayu Berbasiskan Metode Quality Function Deployment (QFD) - Derik Oktarian; Yohanes Yohanes; Satriadi Satriadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The processing of cassava paste is generally done manually, ie by way of cassava that has been boiled and then ground using traditional tool are pestle and mortar to be pasta, pasta process cassava thinned using manual tools to the way in the play with their hands. After the thin manioc paste is then printed, for dried pasta plate drying process using hot sun. Roolpress-grinder machine design is done using quality function deployment method that aims to obtain design parameters in accordance with the wishes of the community. From the results of questionnaires parameter in this design are: cassava processing machines belonging, prices are relatively cheap, easily obtainable spart part, electric motor propulsion engine wear, easy to use process. Of all these parameters based on the results of the test using SPSS17.0 softwere significant value is the selection of the highest mover, with a value corrected item-total correlation was 0.610. In designing the grinder machine-rollpress rollpress used this kind made of metal for food or beverage processing equipment. The dimensions of the machine grinder-roolpress Indonesia Anthropometric Data obtained using the 5th percentile. These dimensions include hip height (height rollpress desk onto the floor) is 98.8 cm long, fore arm span (distance operator when performing a milling process) is 77.6 cm long and ranges of hands to the side (distance operator to reach the second workbench) that is 176.1 cm.Keywords: Cassava, Cassava Processing Machinery Pasta, methods of quality function deployment, anthropometry Indonesian, and questionnaires.